MEASURING THE FUNDAMENTAL ATTRACTIVENESS OF PALM OIL BUSINESS AMIDST THE LEGITIMACY CRISIS: THE MODERATING ROLE OF OIL EXTRACTION RATE ON THE INFLUENCE OF INTEREST COVERAGE RATIO AND EBITDA MARGIN ON STOCK PRICES - Thezar Fiqih Hidayat Hasibuan (PT. Radja Intercontinental Publishing, 2026)
Industry coconut Central Indonesian palm oil at a crossroads paradoxical : in one side face crisis legitimacy scale national follow 4.09 million in order hectares garden palm oil illegal in area forest by Unit Task Forest Area Regulation , while on the other hand recording foreign exchange export highest throughout history amounting to US 35.87 billion by 2025. Research This aim test Is the capital market stable? appreciate the fundamentals of resilience financial issuer plantation palm oil in the middle pressure legitimacy said , with positioning the interest coverage ratio (ICR) and EBITDA margin as predictor price share as well as oil extraction rate (OER) as variables moderation . Balanced panel data collected from ten issuer plantation palm oil on the Indonesia Stock Exchange during period 2023 to first quarter 2026 (40 observations ) and analyzed using moderated regression analysis based on panel data regression with error standard clustered . Estimation results show that ICR and EBITDA margin have an effect positive significant to price OER shares are proven strengthen the influence of EBITDA margin on price shares (β = 88.535; p = 0.011) and behave as moderator pure , but No moderate ICR influence . Simple slopes analysis confirms that sensitivity price share to profitability increase in a way monoton along increase yield . Findings This indicates that investors do differentiation fundamentally based instead of punish industry in a way collectively , so that Power lure business palm oil for perpetrator business rooted in profitability whose credibility amplified by excellence operational agronomist .